Deforestation is one of the global problems of mankind - Yegykian, А. R. (ТДАТУ, 2019)
The opposite of deforestation is reforestation. But we should understand that planting new trees will not solve all the problems. We must remove the causes of deforestation.
Keywords: deforestation; environmental problems; social-economic problems; reforestation